Cyrus the Younger, Greek Envoys, and the so-called Treaty of Boiotios (409–408 BC) - Podrazik, Michał (Anabasis. Studia Classica et Orientalia, 2015)
At the end of the 5 th century BC the Persian Empire and the Hellenes from European Greece maintained rather strong relations. During the so-called Ionian War (413–404 BC), both the Lakedaimonians and the Athenians would send their envoys to Darius II, the Great King of Persia, or to his governors in western Asia Minor, with the hopes of gaining some support and winning the ongoing war. At the beginning of the last decade of the 5 th century BC the Greek ambassadors began their journey to Susa, which coincided with the arrival of the royal son, Cyrus the Younger, to Anatolia. The subject-matter of the paper is to present political relationships between the Iranian prince and the Greek envoys, Athenian and Lakedaimonian in particular, sent to the Great King in the years 409–408 BC.